Prototipo de una interfaz interactiva como herramienta de divulgación para el uso correcto de la publicidad en los espacios públicos del cantón Latacunga. - Chilig Tapia, Elvis Mauricio (2024)
The purpose of following research is to implement a prototype, what serves as a tool for the dissemination and control by advertising in the Latacunga canton, for this, it was used the interactivity use on the website and in turn, it will implement the advertising regulations, established by the institution, this raised based on excessive advertising in different commercial sites, generating alterations in the urban landscape. The aim this project is based on the website analysis and its implements, same, which will be used to the building the prototype, what it is proposed a heuristic test proposed by Nielsen. The project development includes bibliographic research, same, which helps to get knowledge in the websites interactivity, usability and design, likewise, using techniques, such as focus groups, observation sheets, and for testing the website and which complies with all web accessibility standards, it is proposed the TAW tool use and applying an assessment to users and premises owners, they will allow getting information from the website. The prototype development was based on the Design Thinking